2021
DOI: 10.3390/ani11082334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bait on Male White-Tailed Deer Resource Selection

Abstract: Bait is often used to increase wildlife harvest susceptibility, enhance viewing opportunities, and survey wildlife populations. The effects of baiting depend on how bait influences space use and resource selection at multiple spatial scales. Although telemetry studies allow for inferences about resource selection within home ranges (third-order selection), they provide limited information about spatial variation in density, which is the result of second-order selection. Recent advances in spatial capture-recap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Although these methods have been shown to be highly effective, they are labor intensive because they can involve manual interpretation and cross-referencing of thousands of images. Moreover, adult female deer lack unique markings, prohibiting the use of standard SMR models (Johnson et al, 2021). Partially marking the adult female population within our study area permitted a cost-effective sampling method that balanced the tradeoffs between density estimation and logistic constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these methods have been shown to be highly effective, they are labor intensive because they can involve manual interpretation and cross-referencing of thousands of images. Moreover, adult female deer lack unique markings, prohibiting the use of standard SMR models (Johnson et al, 2021). Partially marking the adult female population within our study area permitted a cost-effective sampling method that balanced the tradeoffs between density estimation and logistic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…White‐tailed deer play important cultural, economic, and ecological roles throughout their range, and reliable techniques are needed to monitor deer population dynamics and to guide management decisions. Remote cameras have become increasingly popular monitoring methods for white‐tailed deer due to their low‐cost and non‐invasive nature (Chitwood et al, 2017; Curtis et al, 2009; Jacobson et al, 1997; Johnson et al, 2021; Keever et al, 2017; Roberts et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…An alternative explanation of our results is that the change in observed spatial distributions was the result of using different survey methods (baited versus passive). However, previous studies have demonstrated that sexual segregation is not an artifact of sampling methodology (McCullough et al 1989, Main and Coblentz 1990, Bowyer 2004, and deer distributions are not altered by bait (Johnson et al 2021). Furthermore, baited sites were equally distributed across the landscape allowing all deer to have access to at least one baited site within their home range.…”
Section: Discussionmentioning
confidence: 99%
“…Property 1 focused on white‐tailed deer habitat management, while properties 2 and 3 had a long history of intensive habitat management to promote high densities of northern bobwhite Colinus virginianus . Typical management on the properties included frequent prescribed fire, food plots/supplemental feed, timber management, roller chopping, mowing and seasonal disking (Johnson et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Priesmeyer et al (2012) reviewed past deer baiting papers and concluded that supplemental feeding can disrupt movement patterns, but impacts were highly variable. While baiting has been shown to concentrate animals in specific areas [32,34], it is not fully understood if baiting protocols used for '4-Poster' operations increase site-specific deer densities on the landscape, especially in overpopulated suburban areas. Nor is it well understood how often or during which times deer visit '4-Poster' feeders, which is potentially consequential for their overall utility.…”
Section: Introductionmentioning
confidence: 99%